Pengaruh Service Quality dan Perceived Value terhadap Customer Satisfaction dengan Customer Trust sebagai Variabel Intervening - Cnosta, Cella; Ningrum, Nonik Kusuma; Cahyani, Putri Dwi (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to test whether service quality and perceived value influence customer satisfaction with customer trust as an intervening variable. The research sampled several users of Skintific skincare products. The sampling method used was nonprobability sampling through purposive sampling. Data collection was done using a questionnaire distributed through Google Forms. A total of 244 questionnaires were processed, obtained using a sample size formula depending on the number of indicators and multiplied by 5 to 10. The data was analyzed using multiple regression analysis and processed using SPSS version 25. The results of this research indicate that (1) service quality has a positive and significant influence on customer satisfaction, (2) perceived value has a positive and significant influence on customer satisfaction, (3) service quality has a positive and significant influence on customer trust, (4) perceived value has a positive and significant influence on customer trust, (5) customer trust has a positive and significant influence on customer satisfaction.